Civil Engineering Applications of Ground Penetrating Radar - Benedetto, Andrea (Springer, 2015)
This book, based on Transport and Urban Development COST Action TU1208, presents the most advanced applications of ground penetrating radar (GPR) in a civil engineering context, with documentation of instrumentation, methods and results. It explains clearly how GPR can be employed for the surveying of critical transport infrastructure, such as roads, pavements, bridges and tunnels and for the sensing and mapping of underground utilities and voids. Detailed attention is also devoted to use of GPR in the inspection of geological structures and of construction materials and structures, including reinforced concrete, steel reinforcing bars and pre/post-tensioned stressing ducts. Advanced methods for solution of electromagnetic scattering problems and new data processing techniques are also presented. Readers will come to appreciate that GPR is a safe, advanced, non destructive and noninvasive imaging technique that can be effectively used for the inspection of composite structures and the performance of diagnostics relevant to the entire life cycle of civil engineering works.